An optical measurement method for nanosecond impulse signal monitoring of partial discharge based on the Fabry-Perot interferometer sensing system - Zhang, Jiawei; Wang, Li; Chen, Junhui; Takao, Matsumoto; Diaham, Sombel; Song, Chen (Japanese journal of applied physics, 2022)
Partial discharge (PD) detection in high-voltage power equipment is significant as it provides the earliest information on the degradation characteristics. A fiber-optic Fabry-Perot (F-P) sensor based on a charge-coupled probe is designed to detect PD signals under impulse voltage. When the PD signal acts on the probe, the potential difference induced by the probe leads to the deformation of the piezoelectric diaphragm, which further results in the change of light intensity signal. Thus, PD detection could be realized by converting the light intensity signal into a voltage signal. In this study, the discharge impulse signal under various voltage frequencies (50 Hz, 5 kHz, 10 kHz) has been monitored by the F-P sensor and the ultrahigh-frequency (UHF) antenna. Compared with the UHF antenna, the average sensitivity of PD signals detected by the F-P sensor is increased by 17.2%. It is of great significance for online monitoring of the insulation performance of power equipment. Moreover, the F-P sensor has powerful potential for applications such as electrostatic monitoring in aerospace, the petrochemical industry, and meteorological forecasting.